Dhammic Technology Acceptance Model (DTAM): Extending the TAM Using a Condition of Attachment in Buddhism. (March 2015) - Teo, Timothy; Jarupunphol, Pita
Upadana or a condition of attachment in Buddhism has been widely acknowledged among Buddhists as the root cause of suffering because it underlies human intention and action toward a perceived phenomenon. This article investigates whether the condition of attachment in Buddhism could contribute as an external variable in the Technology Acceptance Model. Participants were 498 students from a university in Southern Thailand. They responded to a 21-item self-report questionnaire on the six variables (perceived usefulness, perceived ease of use, attitude toward use, intention to use, attachment, and actual usage) of a proposed Dhammic Technology Acceptance Model. Results using structural equation modeling revealed that the Dhammic Technology Acceptance Model has a good model fit and that attachment has direct and indirect effects on the actual use of Facebook among students. Implications for theory and further research are discussed.